Public participation in The Security Community of Hua Hin Municipality Prachuabkirikhan: การมีส่วนร่วมของภาคประชาชนในการรักษาความปลอดภัยชุมชนในเขตเทศบาลเมืองหัวหิน จังหวัดประจวบคีรีขันธ์ - แต้มแก้ว สุภาณี (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2018)
This research aimimg to study 1)Level of Public participation in The Security Community of Hua Hin Municipality 2) The relationship between the Public participation in Security Community Factor’s and level of Public participation in Security Community of Hua Hin Municipality Prachuabkirikhan. The sample group were 130 informants from representative people who lives in 4 Communities of Huahin Municipality: Phetsasong Community, Smor rieng Community, Chai Talay Community and Phulsook Community. The Reserch instrument was questionnaire. The statistics used for data analysis, mean, standard devition, Chi-Square, Pearson’s Product Moment Correlation Coefficient and content analysis. The research result were as follows: 1) The level of Public participation in Security Community of Hua Hin Municipality Prachuabkirikhan were overall at a moderate level. When each aspect was considered, it was found that the aspect with highest mean were Participation in benefits and Participation in implementation. The Paticipation in decision-making and Paticipation project monitoring and evaluation were overall at a moderate level. 2) The relationship between the Public participation in Security Community Factor’s and level of Public participation in Security Community of Hua Hin Municipality Prachuabkirikhan were at a highest level with statistical significance at .001 level. When each aspect was considered as a whole were at a high level with statistical significance at .001 level were The strong communities and community acceptance social support